2019
DOI: 10.2147/tcrm.s204841
|View full text |Cite
|
Sign up to set email alerts
|

<p>Glioma-associated radiation retinopathy treated successfully with aflibercept</p>

Abstract: Radiation retinopathy is a chronic, progressive retinal microangiopathy which can occur with variable latency after retina exposure to ionizing radiation used for cancer treatment. It can occur secondary to treatment of nasopharyngeal tumors, as well as intraocular tumors, such as uveal melanoma and retinoblastoma. Several treatment modalities have been reported including intravitreal corticosteroids, intravitreal anti-VEGFs and argon laser photocoagulation. Our purpose is to present a case report of bilateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…In 2017, Pooprasert et al [35] demonstrated improvement in radiation retinopathy in a single case of radiation retinopathy. In 2019, Karagiannis et al [32] utilized primary intravitreal aflibercept and demonstrated improvement in a patient with bilateral peripheral radiation retinopathy and unilateral maculopathy presumed to be related to external beam radiotherapy of an optic nerve glioma. Fallico et al [33], in 2019, utilized intravitreal aflibercept as a primary treatment of 9 patients with radiation maculopathy secondary to treatment of uveal melanoma with ruthenium-106.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2017, Pooprasert et al [35] demonstrated improvement in radiation retinopathy in a single case of radiation retinopathy. In 2019, Karagiannis et al [32] utilized primary intravitreal aflibercept and demonstrated improvement in a patient with bilateral peripheral radiation retinopathy and unilateral maculopathy presumed to be related to external beam radiotherapy of an optic nerve glioma. Fallico et al [33], in 2019, utilized intravitreal aflibercept as a primary treatment of 9 patients with radiation maculopathy secondary to treatment of uveal melanoma with ruthenium-106.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, limited information on the use of intravitreal aflibercept has also shown anatomical and functional benefits. Aflibercept is a human recombinant fusion protein that is extensively used for diabetic macular edema, macular degeneration, central and branch retinal vein occlusions, and other sources of neovascularization within the eye [32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%